Alkene ceramic material as well as preparation method and application thereof

By growing carbide ceramics on the limited area of ​​the graphene surface and assembling the thermal insulation frame of graphene-loaded carbide ceramic nanoparticles, the problem of recrystallization of ceramic materials at extremely high temperatures is solved, and high-efficiency thermal insulation at 2000℃ is achieved and maintain mechanical properties.

CN119430167AActive Publication Date: 2025-02-14ZHEJIANG UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411617821.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Ceramic materials are prone to recrystallization at extremely high temperatures, resulting in a decrease in mechanical properties, an increase in porosity and an increase in thermal conductivity, and cannot effectively insulate the heat in an environment above 1600°C.

Method used

By growing carbide ceramics in situ on the two-dimensional graphene surface, assemble the thermal insulation frame of graphene-loaded carbide ceramic nanoparticles to form an ene-ceramic material, achieving good heat insulation at ultra-high temperature of 2000°C.

Benefits of technology

The olefin material has excellent thermal insulation effect at 2000°C, and the thermal conductivity is significantly improved, while maintaining good mechanical properties and high temperature stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430167A_ABST
    Figure CN119430167A_ABST
Patent Text Reader

Abstract

The invention provides a graphene ceramic material as well as a preparation method and application thereof, a two-dimensional atomic interlayer channel of a graphene oxide film is utilized to adsorb ceramic precursor salt, an atomic-level hybrid graphene oxide film is realized, and finally, carbide is grown on graphene in situ through a high-temperature reaction, so that the preparation of a graphene ceramic hybrid material is realized. The internal microstructure of the prepared graphene ceramic material presents atomic-level hybridization of graphene ceramic carbide, can realize layer-by-layer step-by-step protection of heat, shows extremely low thermal conductivity, has relatively high multi-layer heat radiation shielding capability at ultrahigh temperature, ensures excellent heat insulation capability at ultrahigh temperature, and can be used for preparing the graphene ceramic material. And huge application potential is shown in the extreme thermal protection field of ultra-high-speed aircrafts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to an olefin ceramic material and a preparation method and application thereof. Background Art

[0002] Ceramic materials, including ceramic aerogels, are widely used in many high-temperature environments due to their excellent mechanical strength, chemical stability and high-temperature resistance, especially in aerospace, automotive industry and energy production. However, despite the many advantages of ceramic materials, their application at extremely high temperatures is affected by the phenomenon of recrystallization. Recrystallization refers to the process in which the microstructure of a material changes due to the migration of atoms or molecules at high temperatures. This change may lead to adverse effects such as decreased mechanical properties, increased porosity and increased thermal conductivity. Although this high temperature limit varies depending on the specific composition and microstructure of the material, in general, in order to effectively inhibit the occurrence of recrystallization, most existing thermal insulation ceramic materials can only be used in environments below 1600°C. Summary of the invention

[0003] The present invention proposes an olefin ceramic material to solve the problem that ceramic materials will recrystallize under high temperature conditions to form large crystals, enlarge pores, increase thermal conductivity, and cannot be insulated at ultra-high temperatures of 1600°C. The material achieves good thermal insulation at ultra-high temperatures of 2000°C by in-situ confined growth of carbide ceramics on the surface of two-dimensional graphene and assembling a thermal insulation frame of graphene-loaded carbide ceramic nanoparticles.

[0004] Graphene has an extremely high thermal conductivity, which means that it can conduct heat efficiently but cannot block heat transfer. In the present invention, an excellent thermal insulation effect is achieved by inserting a ceramic particle layer anchored by graphene between continuous graphene layers. The ceramic layer can reduce heat conduction in the vertical direction and thus insulate, while graphene can efficiently conduct heat laterally and evenly distribute heat. At the same time, the dense structure of graphene has a two-dimensional shielding effect that can reduce thermal radiation and can effectively enhance the thermal insulation effect. In addition, the excellent mechanical properties of the aerogel structure give the olefin ceramic aerogel excellent mechanical compression and elastic recovery stability against thermal expansion. In particular, when the density of the ceramic particle layer is low and the particles are discontinuous, this olefin ceramic material exhibits more excellent thermal insulation properties.

[0005] One of the technical solutions of the present invention is to provide an olefin ceramic material, which includes ceramic nanoparticles; and the ceramic nanoparticles are confined and grown between graphene layers; the size of the ceramic nanoparticles is between 1 and 50 nm. The anchoring of the ceramic nanoparticles by graphene effectively avoids the problem of ceramic recrystallization, forming large crystals, and then the problem of decreased thermal insulation performance caused by enlarged voids, so that the olefin ceramic material of the present invention still has thermal insulation stability under high temperature conditions.

[0006] Furthermore, the olefin ceramic material is olefin ceramic aerogel, and the porous structure can generate convection and enhance the heat insulation effect.

[0007] The second technical solution of the present invention is to provide a method for preparing an olefin ceramic material, which specifically comprises the following steps: (1) Immerse the graphene oxide film in the precursor salt solution for 6 hours to allow the precursor salt ions to adsorb between the surface layers of the graphene oxide. Utilize the anchoring effect of the oxygen-containing groups in the graphene oxide film on the two-dimensional material precursor ions to achieve two-dimensional restricted growth of carbides in the two-dimensional atomic channel, thereby ensuring the stable dispersion of ceramic particles;

[0008] In order to ensure that the graphene oxide can retain its own structure during the high-temperature carbonization process instead of being completely converted into carbides, the precursor salt should be kept at a low concentration that can be evenly distributed between the graphene layers. This concentration is related to factors such as the thickness and density of the graphene oxide film used, and those skilled in the art can determine the concentration range through simple experiments.

[0009] (2) Drying at room temperature to obtain a hybrid film of graphene oxide and precursor salt; (3) Carbonization at 1500-2800°C for 4 hours in a tubular furnace under inert atmosphere to carbonize the precursor salt in situ and form carbide ceramic particles on the surface of graphene.

[0010] Furthermore, the precursor salt solution in step 1 includes one or more of zirconium chloride, tantalum chloride, niobium chloride, titanium chloride, and hafnium chloride.

[0011] Furthermore, before the carbonization treatment, the hybrid membrane is subjected to a foaming treatment to obtain an olefin-ceramic material having a porous structure; the foaming treatment is specifically as follows: (1) subjecting the hybrid membrane to solution-plastic foaming in a 30 wt % hydrazine hydrate solution; (2) The surface hydrazine hydrate solution is then washed away with ethanol and dried at room temperature to obtain a hybrid aerogel of graphene oxide and metal precursor salt.

[0012] Furthermore, the solution-plastic foaming time is 30 minutes.

[0013] The third technical solution of the present invention is to provide an application of ethylene ceramic material in super thermal insulation, which is particularly suitable for thermal insulation above 1600 degrees Celsius.

[0014] The beneficial effects of the present invention are: The present invention overcomes technical prejudice, uses graphene with excellent thermal conductivity in the field of thermal insulation, and combines the structural design of thermal insulation ceramic nanoparticles to obtain super thermal insulation olefin ceramic materials, which greatly improves the thermal insulation effect and high-temperature stability of the materials. The thermal conductivity of the prepared tantalum carbide olefin ceramic material is 21.1 mW / mK at room temperature and 213.4 mW / mK at 2000°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The scanning electron microscope and element distribution diagram of the tantalum carbide ceramic aerogel prepared in Example 1 before and after being treated at 2000°C.

[0016] Figure 2 This is a large-scale physical picture of the tantalum carbide ceramic aerogel prepared in Example 1.

[0017] Figure 3 This is the SEM image of the tantalum carbide ceramic aerogel prepared in Example 1.

[0018] Figure 4 This is the SEM image of the carbonized zirconium ene ceramic aerogel prepared in Example 3.

[0019] Figure 5 This is the thermal conductivity of the tantalum carbide ceramic aerogel prepared in Example 1. DETAILED DESCRIPTION

[0020] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0021] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0022] In the preparation method of the present invention, the precursor salt solution should be maintained at a concentration that allows graphene structures to remain after carbonization of the aerogel and enables ceramic nanoparticles to be evenly distributed between graphene layers. A person skilled in the art can determine the appropriate concentration by performing a simple test based on the thickness of the graphene film used.

[0023] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0024] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0026] Example 1 The graphene oxide film (purchased from Hangzhou Gaoxin Technology Co., Ltd.) was immersed in a 10 mg / g tantalum chloride salt solution for 6 hours, and after drying at room temperature, a hybrid film of graphene oxide and tantalum chloride was obtained, which was then placed in a 30% hydrazine hydrate solution for dissolution-plastic foaming. After foaming for 30 minutes, it was taken out and the residual solvent on its surface was washed off with ethanol. After being placed at room temperature for drying, a hybrid aerogel of graphene oxide and tantalum chloride hydrate was obtained, which was placed in a tubular furnace under inert atmosphere protection at 1500 degrees Celsius for 4 hours to obtain tantalum carbide ceramic aerogel. Figure 1 The scanning electron microscope and element distribution diagram of tantalum carbide ceramic aerogel before and after treatment at 2000℃ show that the tantalum element is still evenly distributed in the porous structure composed of graphene sheets after treatment at 2000℃, and the ceramic particles between the graphene layers have not aggregated, indicating that under high temperature conditions, the ceramic particles have not aggregated during the recrystallization process and can maintain the original structure. Figure 3 As shown, the aerogel has a dense network structure, and the carbon and metal elements are evenly distributed in the aerogel. The density of the aerogel is 8.86 mg / cm 3 , after 10,000 cycles at 99% compressive strain, the plastic deformation is only 4.5%. Figure 5 The thermal conductivity of the tantalum carbide ceramic aerogel prepared in this example is 21.1 mW / mK at room temperature and 213.4 mW / mK at 2000°C, which has excellent thermal insulation effect.

[0027] Example 2 The graphene oxide film (purchased from Hangzhou Gaoxin Technology Co., Ltd.) was immersed in a 10 mg / g tantalum chloride salt solution for 6 hours, and after drying at room temperature, a hybrid film of graphene oxide and tantalum chloride was obtained. The hybrid film was placed in a tubular furnace under inert atmosphere protection at 1600 degrees Celsius for 4 hours to obtain tantalum carbide ceramic material.

[0028] Under high temperature conditions, the ceramic particles do not agglomerate during the recrystallization process and can maintain their original structure. The thermal conductivity at room temperature is 23.5mW / mK, and the thermal conductivity at 2000℃ is 243.6mW / mK, which has excellent thermal insulation effect.

[0029] Example 3 The graphene oxide film (purchased from Hangzhou Gaoxin Technology Co., Ltd.) was immersed in a 10 mg / g zirconium chloride salt solution for 6 h, and then dried at room temperature to obtain a hybrid film of graphene oxide and zirconium chloride. It was then placed in a 30% hydrazine hydrate solution for solution-plastic foaming. After foaming for 30 min, it was taken out and the residual solvent on its surface was washed away with ethanol. After being placed at room temperature for drying, a hybrid aerogel of graphene oxide and zirconium chloride hydrate was obtained. It was placed in a tubular furnace under inert atmosphere protection at 2800 degrees Celsius for 4 h to prepare carbonized zirconium ene ceramic aerogel. Its SEM image and element distribution are shown in Figure 2. Figure 4 As shown, the aerogel has a dense network structure, and the carbon and metal elements are evenly distributed in the aerogel. The density of the aerogel is 9.6 mg / cm 3 After 10,000 cycles of 99% compressive strain, the plastic deformation is only 6.5%. The thermal conductivity at room temperature is 25.1 mW / mK, and the thermal conductivity at 2000°C is 343.8 mW / mK.

[0030] Example 4 The same as Example 2, except that tantalum chloride was replaced by a mixed solution of zirconium chloride and tantalum chloride to prepare zirconium carbide tantalum olefin ceramic aerogel. The aerogel density was 7.6 mg / cm 3 After 10,000 cycles of 99% compressive strain, the plastic deformation is only 1.2%. The thermal conductivity at room temperature is 17.4 mW / mK, and the thermal conductivity at 2000°C is 171.0 mW / mK.

[0031] Comparative Example 1 The graphene oxide film (purchased from Hangzhou Gaoxi Technology Co., Ltd.) was immersed in a 50 mg / g zirconium chloride salt solution for 6 hours, and after drying at room temperature, a hybrid film of graphene oxide and zirconium chloride was obtained. It was then placed in a 30% hydrazine hydrate solution for dissolution-plastic foaming. After foaming for 30 minutes, it was taken out and the residual solvent on its surface was washed off with ethanol. After being placed at room temperature for drying, a hybrid aerogel of graphene oxide and zirconium chloride hydrate was obtained. It was placed in a tubular furnace under inert atmosphere protection at 2800 degrees Celsius for 4 hours to prepare carbonized zirconium ene ceramic aerogel. The thermal conductivity of the aerogel at room temperature is 56 mW / mK. At 2000°C, the ceramic crystals reassemble, the thermal conductivity increases significantly, and the thermal insulation effect is poor.

[0032] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. An olefin ceramic material, characterized in that: The invention comprises ceramic nanoparticles, and the ceramic nanoparticles are confinedly grown between graphene layers; and the size of the ceramic nanoparticles is between 1 and 50 nm.

2. The olefin ceramic material according to claim 1, characterized in that: The olefin ceramic material is olefin ceramic aerogel.

3. A method for preparing an olefin ceramic material as claimed in claim 1, characterized in that: The specific steps include: (1) Immersing the graphene oxide film in a precursor salt solution for 6 hours to allow the precursor salt ions to be adsorbed between the surface layers of the graphene oxide; (2) Drying at room temperature to obtain a hybrid film of graphene oxide and precursor salt; (3) Carbonizing at 1500-2800°C for 4 hours in an inert atmosphere in a tubular furnace to in situ carbonize the precursor salt on the graphene surface to obtain a carbide olefin ceramic material.

4. The preparation method according to claim 3, characterized in that: The precursor salt solution in step 1 includes one or more of zirconium chloride, tantalum chloride, niobium chloride, titanium chloride, and hafnium chloride.

5. The method according to claim 3, characterized in that: Before the carbonization treatment, the hybrid membrane is also subjected to a foaming treatment to obtain an olefin-ceramic aerogel material; the foaming treatment is specifically as follows: (1) subjecting the hybrid membrane to solution-plastic foaming in a 30 wt % hydrazine hydrate solution; (2) The surface hydrazine hydrate solution is then washed away with ethanol and dried at room temperature to obtain a hybrid aerogel of graphene oxide and metal precursor salt.

6. The preparation method according to claim 5, characterized in that: The time of the dissolution-plastic foaming in step 1 is 30 minutes.

7. Use of the olefin ceramic material as claimed in claim 1 in super thermal insulation.

Citation Information

Patent Citations

  • Graphene / leucite nano-composite ceramic material generated in high-temperature in-situ mode and preparation method thereof

    CN104529429A

  • Three-dimensional porous ceramic-graphene bulk composite material and preparation method thereof

    CN108117410A

  • Preparation method and application of graphene-based composite aerogel

    CN115724646A

  • Preparation method of graphene composite porous silicon oxide ceramic

    CN116063099A

  • Piezo-electric ceramic composite by using grapheme oxide

    KR1020140134930A